The Influence of Body Shape Perception on Physical Activity, Screen Time, and Eating in Black School-Aged Immigrant Children - Gunter, Ashley (Université d'Ottawa / University of Ottawa, 2016)
Background: Previous studies revealed both parents and children tend to misperceive the child’s body shape. Body shape perception has been found to influence modifiable lifestyle habits; however, these relationships have been scarcely studied. Objective: To determine the influence of body shape perception on physical activity, screen time, and maternal feeding practices. Methods: A total of 259 mother-child dyads were interviewed. Data were collected during structured interviews and included questions regarding body shape perception, physical activity, screen time, and maternal feeding practices. Results: Roughly 50% of mothers and children misperceived the child’s body shape. Children’s physical activity and certain maternal feeding practices were found to be influenced by body shape perception; however, body shape perception did not significantly influence children’s screen time. Conclusion: Body shape misperception was frequent among this group of mothers and children. As well, body shape perception seemed to have influenced certain modifiable lifestyle habits.
Keywords: Black children; Body shape perception; Physical activity; Screen time; Eating